TEACHING EFL SPEAKING SKILLS: A SELF-STUDY OF EFFECTIVE LESSON PLANNING AND DELIVERY - The, Hery Yanto (UICELL, 2023)
English as a Foreign Language (EFL) teachers will encounter challenges while instructing students from diverse backgrounds. They will overcome these challenges when they use strategically designed, well-conducted lessons that have the potential to enhance students' engagement and proficiency in communication greatly. This research studied the best practices in planning and delivering English-speaking lessons to EFL students in China and Indonesia, utilizing a self-analysis of the teaching practice approach. This study clarifies the principles underlying the inception of two speaking exercises, namely "Friendship Soup" and "Chain Story," and provides precise insight into the techniques employed in students speaking practices. The findings emphasized the students' enthusiastic engagement, favorable dispositions towards the assignments, and favorable responses to the prompt feedback they got. Another advantageous result of such tasks is the enhanced proficiency of the students in speaking. By looking at EFL speaking activities from a global point of view, this study adds to what is known by making them suitable for students from a range of backgrounds and points of view. The findings have significance for educators seeking to enhance student involvement and selfassurance in speaking to others and to improve their level of EFL instruction in diverse settings. Keywords: Self-Study, Teaching Practice, Speaking Skills